Artificial Intelligence dalam Pengukuran dan Penilaian Pendidikan: Kajian Literatur dari Perspektif Inovasi Evaluatif - Sabri, Muhammad; Wais, Abdul (Jurnal Evaluasi Pendidikan, 2025)
The use of AI in educational measurement and assessment has become an inevitability that we must accept. This study aims to examine the role of AI in revolutionizing educational measurement and assessment as a driver of innovation in assessment instruments, processes, and policies. This study is a systematic literature review with a narrative-critical approach conducted through nine main stages: 1) Review of core concept definitions, 2) Identification of AI Technologies and Applications, 3) Review of Current Conditions and AI Integration Methodologies, 4) Analysis of Benefits and Advantages of AI, 5) Investigation of Challenges, Limitations, and Ethical Considerations, 6) Exploration of AI Contributions to Evaluative Innovation, 7) Synthesis of Findings, Trends, and Research Gaps, 8) Identification of Future Directions and Implications, 9) Credibility Analysis. The results of the study indicate that AI has revolutionized the assessment process by enabling automated assessment and instant feedback, thereby improving academic integrity and simplifying administration